2022
DOI: 10.3390/polym14224967
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of the Influence of Expanded Vermiculite on the Foaming Process and Selected Properties of Composite Rigid Polyurethane Foams

Abstract: This article presents the results of research on obtaining new polyurethane (PUR) foams modified with thermally expanded vermiculite. The filler was added in amount of 3 wt.% up to 15 wt.%. The additionally applied procedure of immersion the non-organic filler in H2O2 was performed to increase the exfoliation effect of thermally treated mineral and additional oxidation the surfaces. The effect of fillers on foaming process, cell structure, thermal insulation, apparent density, compressive strength, thermal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
3
2
0
Order By: Relevance
“…However, the ignition time of LigW/LG ratio 1/1 and 1/2 particles increased up to 5 s and 6 s, respectively, which was determined by the cellular structure and thermal conductivity of the resulting foam composites. Similar observations were made by Barczewski et al [ 44 ], who studied the influence of expanded vermiculite on the fire behaviour of modified polyurethane foams.…”
Section: Resultssupporting
confidence: 86%
“…However, the ignition time of LigW/LG ratio 1/1 and 1/2 particles increased up to 5 s and 6 s, respectively, which was determined by the cellular structure and thermal conductivity of the resulting foam composites. Similar observations were made by Barczewski et al [ 44 ], who studied the influence of expanded vermiculite on the fire behaviour of modified polyurethane foams.…”
Section: Resultssupporting
confidence: 86%
“…The XRD pattern was similar to previous publications on expanded vermiculite, the peaks at 2θ = 27.2° and 34.32° correspond to d-spacing of 3.3 Å, and 2.6 Å, respectively [34]. The diffraction peak at around 60 o is ascribed to the (060) plane indicating the trioctahedral type kind of the vermiculite structure [34][35][36]. Typically, vermiculite can exist in either dioctahedral or trioctahedral forms, although the trioctahedral variety is more prevalent in soils that have a similar structure to mica [37].…”
Section: Characterization Of Expanded Vermiculitesupporting
confidence: 87%
“…2a. The XRD pattern was similar to previous publications on expanded vermiculite, the peaks at 2θ = 27.2° and 34.32° correspond to d-spacing of 3.3 Å, and 2.6 Å, respectively [34]. The diffraction peak at around 60 o is ascribed to the (060) plane indicating the trioctahedral type kind of the vermiculite structure [34][35][36].…”
Section: Characterization Of Expanded Vermiculitesupporting
confidence: 84%
“…The volumetric percentage of closed cells increased with the addition of particles, regardless of the amount of LG used for modification. However, Barczewski et al [ 35 ] showed that the incorporation of expanded vermiculite resulted in a different tendency. The thermal conductivity was higher for composite foams with the highest closed-cell content, while Członka et al [ 36 ] indicated that walnut shell filler improved the thermal conductivity of composite foams with the highest content of closed cells.…”
Section: Resultsmentioning
confidence: 99%